2015
DOI: 10.1542/peds.2014-2169
|View full text |Cite
|
Sign up to set email alerts
|

Development of Hospital-Based Guidelines for Skeletal Survey in Young Children With Bruises

Abstract: OBJECTIVE: To develop guidelines for performing an initial skeletal survey (SS) for children ,24 months of age presenting with bruising in the hospital setting, combining available evidence with expert opinion. METHODS:Applying the Rand/UCLA Appropriateness Method, a multispecialty panel of 10 experts relied on evidence from the literature and their own clinical expertise in rating the appropriateness of performing SS for 198 clinical scenarios characterizing children ,24 months old with bruising. After a mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 39 publications
(15 reference statements)
0
15
0
1
Order By: Relevance
“…13 This methodology was previously used to identify scenarios in which SS is appropriate and necessary for children <2 years old with fractures or bruises. 14,15 RAM is a modified Delphi process that informs clinical decision-making by combining the evidence from a systematic review of the literature with clinical expertise to determine the benefitharm ratio of tests and screening procedures for various clinical scenarios. Unlike similar consensus methods, RAM provides experts with an opportunity to discuss their clinical judgments with each other and modify scenarios accordingly.…”
Section: Methodsmentioning
confidence: 99%
“…13 This methodology was previously used to identify scenarios in which SS is appropriate and necessary for children <2 years old with fractures or bruises. 14,15 RAM is a modified Delphi process that informs clinical decision-making by combining the evidence from a systematic review of the literature with clinical expertise to determine the benefitharm ratio of tests and screening procedures for various clinical scenarios. Unlike similar consensus methods, RAM provides experts with an opportunity to discuss their clinical judgments with each other and modify scenarios accordingly.…”
Section: Methodsmentioning
confidence: 99%
“…The frequency of abuse alters between 18-24% in patients with trauma in different studies. 11,14,15 These studies focused on more well-known trauma such as head trauma and fractures related to abuse; however, in our study, not only traumas but also burns and poisonings that might be related to abuse were taken into consideration. Gencer et al 13 found the rate of the suspected abuse or definitive abuse as 16% investigating the abuse in any kind of home accidents including falling down, foreign object ingestion, intoxication, burn, electrical shock and others.…”
Section: Discussionmentioning
confidence: 99%
“…For all these reasons, training the physicians dealing with children will improve their ability in diagnosing the abuses in the early period and may reduce the recurrences and deaths. [9][10][11] In recent medical literature, medical evaluation of child abuse has received careful consideration because of specialists' increased awareness. [1][2][3]5,9 When abuse is suspected concerning the patients' history and/or physical examination, patients should be evaluated by screening methods, and they should be directed to the specialists.…”
mentioning
confidence: 99%
“…beeinträch-tigen) unterschieden werden. Bestimmte Formen der Kindesmisshandlung haben als spezifische Syndrome Eingang in die medizinische Fachliteratur gefunden ("Battered Child-Syndrom", "Shaken Baby Syndrome" (SBS) und das "Münchhausen-by-proxy-Syndrom" [8, 22,23] Bei Kopfverletzungen ist im Notfall immer die zerebrale Computertomographie (cCT) die Methode der ersten Wahl; in weniger dringlichen Fällen kann bzw. sollte eine cerebrale Kernspintomografie (cMRT) zur Reduktion der Strahlenbelastung durchgeführt werden.…”
Section: Kindesmisshandlung Und Vernachlässigung: Terminologieunclassified